PENERAPAN METODE COOPERATIVE SCRIPT DALAM MENINGKATKAN KEAKTIFAN BERBICARA PADA PEMBELAJARAN PAK SISWA KELAS VB DI SD KRISTEN MALANGO’ TAGARI - Pika Rampa; Melisa Pakombong (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Cooperative comes from the word cooperate which means working together, helping, mutual cooperation. Meanwhile, from the word cooperation which means cooperation, partnership cooperatives. So the cooperative script method is a learning strategy where students study in small groups that have different abilities, where students work in pairs and take turns verbally summarizing the parts of the material being studied, so in this learning process the cooperative script method is used. This research is a class action research (CAR). The subjects of this study were researchers as teachers and VB class students at SD Kristen Malango' Tagari, totaling 20 people, 5 boys and 15 girls. Data collection techniques were carried out by literature study and field studies consisting of observation and documentation. The method used in data analysis techniques is data reduction, presenting data and drawing conclusions. The results showed that there was activeness in speaking, especially in the subject of Christian Religious Education for class VB SD Kristen Malango' Tagari, namely the value of students' active speaking in cycle I reached an average value of 60.38%, the value of students' active speaking in cycle II was an average of 7, 98%.